Revenue Mobilization for a Resilient and Inclusive Recovery in the Middle East and Central Asia - Verdier, Genevieve; Muthoora, Priscilla; Rayner, Brett; Vellutini, Charles (Washington, D.C. : International Monetary Fund, 2022)
Domestic revenue mobilization has been a longstanding challenge for countries in the Middle East and Central Asia. Insufficient revenue has often constrained priority social and infrastructure spending, reducing countries' ability to reach the Sustainable Development Goals, improve growth prospects, and address climate related challenges. Moreover, revenue shortfalls have often been compensated by large and sustained debt accumulation, raising vulnerabilities in some countries, and limiting fiscal space to address future shocks. The COVID-19 pandemic and the war in Ukraine have compounded challenges to sustainable public finances, underscoring the need for revenue mobilization efforts. The recent global crises have also exacerbated existing societal inequalities and highlighted the importance of raising revenues in an efficient and equitable manner. This paper examines the scope for additional tax revenue mobilization and discusses policies to gradually raise tax revenue while supporting resilient growth and inclusion in the Middle East and Central Asia. The paper's main findings are that excluding hydrocarbon revenues, the region's average tax intake lags those of other regions; the region's fragile and conflict-affected states (FCS) face particular challenges in mobilizing tax revenue; In general, there is considerable scope to raise additional tax revenue; countries have made efforts to raise tax collection, but challenges remain; tax policy design, notably low tax rates and pervasive tax exemptions, is an important factor driving tax revenue shortfalls; weak tax compliance, reflecting both structural features and challenges in revenue administration, also plays a role; and personal income tax systems in the region vary in their progressivity-the extent to which the average tax rate increases with income-and in their ability to redistribute income. These findings provide insights for policy action to raise revenue while supporting resilient growth and inclusion. The paper's analysis points to these priorities for the region to improve both efficiency and equity of tax systems: improving tax policy design to broaden the tax base and increase progressivity and redistributive capacity; strengthening revenue administration to improve compliance; and implementing structural reforms to incentivize tax compliance, formalization, and economic diversification.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Equity and Justice; Inequality; Other Normative Criteria and Measurement